Building condition assessment: adjustments of the Building Performance Indicator (BPI) for university buildings in Brazil - Leite, Francisco Morato (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2019)
The Building Performance Indicator (BPI), not fully applied in Brazil, expresses objectively the overall condition of a building based on the performance assessment of the building systems that comprise it. Although BPI was originally developed for hospital facilities, it can be used in different types of buildings since its methodology is generic. The objective of the study is to adjust the BPI to allow its application in the maintenance management of Brazilian university buildings. The stages of the research consist of (1) adjusting the factors and criteria that comprise the BPI; (2) implementing the adapted BPI; and (3) verifying its utility and ease of use. The adjustment and implementation included a building for classrooms and another that houses a teaching and research laboratory, both located at University X. The results obtained allowed the comparison of the overall condition between the inspected buildings, which establishes the intervention priority helping to adopt the most adequate maintenance strategy.